2009
DOI: 10.1177/1062860609351236
|View full text |Cite
|
Sign up to set email alerts
|

Crew Resource Management Improved Perception of Patient Safety in the Operating Room

Abstract: To improve safety in the operating theater, a company of aviation pilots was employed to guide implementation of preprocedural briefings. A 5-point Likert scale survey that assessed the attitudes of operating room personnel toward patient safety was distributed before and 6 months following implementation of the briefings. Using Mann-Whitney analysis, the survey showed a significant (P < .05) improvement in 2 questions (of 13) involving reporting error and 2 questions (of 11) involving patient safety climate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 7 publications
0
57
0
1
Order By: Relevance
“…For example, studies that used interprofessional education activities involved interactive seminars, workshops or team-based simulation [20][21][22][23]. Often these educational interventions employed TeamSTEPPS or CRM (crisis resource management) approaches [24][25][26][27]. Studies reporting the use of interprofessional practice interventions tended to employ team checklists [28][29], team briefings [30,31] or patient safety rounds [32,33].…”
Section: Insert Table 2 About Herementioning
confidence: 99%
“…For example, studies that used interprofessional education activities involved interactive seminars, workshops or team-based simulation [20][21][22][23]. Often these educational interventions employed TeamSTEPPS or CRM (crisis resource management) approaches [24][25][26][27]. Studies reporting the use of interprofessional practice interventions tended to employ team checklists [28][29], team briefings [30,31] or patient safety rounds [32,33].…”
Section: Insert Table 2 About Herementioning
confidence: 99%
“…Interruptions and distractions are a major threat facing flight crews and cannot be different for the teams of trauma surgeons [14][15][16][17][18][19][20] . In the U.S., reports of the Programme of Action for Aviation Safety shows that 14% of the crew include reference to one interruption or distraction 21 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Human factors (distractions), specifically, are usually presented with an overview, sometimes underestimating their influence in the event of errors 8,19,31 .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Studies has shown that second pilots and nurses valued CRM communication training more positive than their counterparts higher in the hierarchy (i.e. surgeon and captain in the cockpit) [17,18]. In addition, crews on board navy ships are organised hierarchically, from master and downwards.…”
Section: Theory Crew Resource Management and Speak Up Behaviourmentioning
confidence: 99%
“…Different positions in hierarchy may give different result. Gore et al [17] and Carney et al [18] reported that surgeons and captains in the cockpit did not see the need for CRM training compared to team members further down the hierarchical ladder.…”
Section: Hypothesismentioning
confidence: 99%